PENGARUH KUALITAS PELAYANAN DALAM PENANGGULANGAN PRA-KRISIS KASUS DI MEDIA SOSIAL TERHADAP CITRA PT KCI - Muthia Handayani; Anita Savitri Arfahsita; Nabila Jafani Ladybo (Institut Pertanian Bogor, 2020)
This study aims to determine the effect of service quality in handling pre-crisis cases through social media on the image of PT KCI. The method used is a quantitative method using a semantic differential scale. The analytical method used is a simple linear regression analysis method. The results showed that commuter line users assessed the quality of service in handling crisis provided by PT KCI. The empathy variable is a concept that plays an important role in determining the company's image in crisis communication. The implication of this research is that companies need to maintain and improve service quality in handling crisis on social media so that the company's image improves. In the context of development communication, companies need to have empathy for users in order to be able to carry out effective crisis communication.